2018
DOI: 10.1371/journal.pone.0207021
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight of institutional births in Cambodia: Analysis of the Demographic and Health Surveys 2010-2014

Abstract: BackgroundLow birth weight (LBW), an important risk factor for early childhood mortality and morbidity, is a major public health concern in developing countries including Cambodia. This study examined the prevalence of LBW across provinces in Cambodia and changes over time, and identified the factors associated with such condition.MethodsWe used children datasets from Cambodia Demographic and Health Survey (CDHS) 2010 and 2014. There were 3,522 children and 4,991 children in both surveys. Maps illustrating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
6
11
1
1
Order By: Relevance
“…In this study, mothers who attended primary, secondary, and higher educational levels less likely deliver SBW babies compared to illiterate mothers. This finding is consistent with a study conducted in Cambodia using DHS data, further analysis of 2011 EDHS, and cohort studies conducted in southern Ethiopia ( 27 29 ). Having a higher educational level had a protective effect in a way that educated women have a higher possibility of making household decisions and have access to a nutritious diet during pregnancy that would, in turn, improve their body's composition which influences infant weight.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, mothers who attended primary, secondary, and higher educational levels less likely deliver SBW babies compared to illiterate mothers. This finding is consistent with a study conducted in Cambodia using DHS data, further analysis of 2011 EDHS, and cohort studies conducted in southern Ethiopia ( 27 29 ). Having a higher educational level had a protective effect in a way that educated women have a higher possibility of making household decisions and have access to a nutritious diet during pregnancy that would, in turn, improve their body's composition which influences infant weight.…”
Section: Discussionsupporting
confidence: 91%
“…It is well-known that low birth weight is negatively associated with a variety of health outcomes, such as lower immune levels, a higher risk of diarrhea and undernutrition, and difficulties of catch-up in child body growth [ 28 ]. The latest national demographic and health survey in Cambodia revealed that the prevalence of low birth weight in rural areas was significantly higher than in urban areas, and that mothers with low education were more likely to give birth to low birth weight children [ 29 ]. The low literacy rate among rural Cambodian women is still a serious problem and an indicator of social and medical disadvantage; however, in recent decades, the literacy rate has been improving [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every year, around 20.5 million babies are born with a low birthweight (LBW: birthweight < 2500 g) worldwide, 80% of whom are born in low- and middle-income countries (LMICs) [ 1 ]. LBW babies are at higher risk of mortality during the neonatal and postnatal periods, plus childhood morbidity, including stunting, developmental delay, and adult-onset diabetes and heart disease [ 1 3 ]. Accurate birthweight measurement is important for the identification of individual risk (e.g.…”
Section: Introductionmentioning
confidence: 99%